Investment Linkages and Incentives : Promoting Technology Transfer and Productivity Spillovers from Foreign Direct Investment - Sabha, Yassin; Liu, Yan; Douw, Wim (World Bank, Washington, DC, 2020)
This note seeks to provide an overview of investment incentive policy as a tool for Governments seeking to promote technology transfer and productivity spillovers by multinational enterprises (MNEs) in the host economy to local firms and suppliers. It summarizes international experiences to demonstrate what has worked and what has not worked, as well as the advantages and disadvantages of different investment incentive schemes. Evidence suggests that backward linkages between MNEs and local suppliers are the most important channels for technology and productivity spillovers to local firms (Jordaan et al, 2020). Furthermore, backward linkages offer an important avenue for ambitious local firms to integrate into Global Value Chains (GVCs). However, several market failures and challenges often prevent backward linkages from materializing. Policy makers can use investment incentives and other policy tools to help address these challenges. This note highlights examples of investment incentive schemes used by Governments, as well as their pros and cons.